Workshop Klinis: Trik Lolos PKM (Program Kreativitas Mahasiswa) untuk Mahasiswa Se-Karesidenan Madiun - Harida, Ratri; Kartikaputra, Tomy; Arkam, Rohmad; Ro'is, Syamsuddin (Empowerment: Jurnal Pengabdian pada Masyarakat, 2025)
Based on documentation studies at STKIP PGRI Ponorogo, there is the fact that the quantity of PKM proposal submissions in 2023 is <70% of last year's DIKTI PKM acceptance quota. This fact needs special attention so that the proposal acceptance quota can be utilized optimally and utilized by students. Of course, this fact must be followed up immediately in the form of a clinical workshop activity for preparing PKM proposals with the theme "Clinical Workshop: Tricks to Pass PKM (Student Creativity Program) for Students throughout the Madiun Province". This activity will be held at Graha Saraswati STKIP PGRI Ponorogo. Implementation of Community Service is carried out offline in three sessions, namely socialization sessions, training and mentoring sessions, and monitoring and evaluation sessions. Participants in the Clinical Workshop: Tricks for Passing the PKM (Student Creativity Program) for Madiun Residency Students, stated that they felt more prepared and confident in taking part in the PKM competition after taking part in this activity. Apart from that, they also stated that the material presented was useful and could help them in preparing quality PKM proposals. Keywords: tricks, Students Creativity Program , writing, workshop